ECONOPHYSICS APPLICATION IN STOCK PRICE TREND PREDICTION ANALYSIS IN THE INDONESIAN COAL SECTOR USING A RESTRICTED BOLTZMANN MACHINE AS A FEATURE EXTRACTOR - Graham, Ariel
Econophysics is an interdisciplinary field that incorporates physics to address pheno- mena within economic systems, with one key focus being the analysis of financial mar- kets. Financial market prediction is crucial for investors’ financial decision-making.